Pengaruh Minat Belajar dan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Siswa SMP Negeri 2 Sendang - Wahyu, Betklin; Suja'i, Imam Sukwatu (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Education is an important aspect of human life and it cannot be denied that education itself is the main factor in introducing humans to achieve knowledge. Education not only builds a person's knowledge and skills but plays an important role in building human character and mentality. The research method used was descriptive quantitative with the research object being students of SMP Negeri 2 Sendang. The population used was 90). The sampling technique for this research used a Nonprobability Sampling design. Based on the results of the multiple linear regression analysis, a linear equation Y 7.247 + 0.477 X1 + 0.383 b1 0.477 is the magnitude of the regression coefficient for the independent variable Learning Interest (X1). This means that every time there is an addition or increase in interest in learning by one unit, the dependent variable Learning Outcomes (Y) will increase by 0.477 assuming the other variables are constant.